2018
DOI: 10.1101/437087
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Metatranscriptomics and nitrogen fixation from the rhizoplane of maize plantlets inoculated with a group of PGPRs

Abstract: 24The free-living soil bacteria that are beneficial for the growth of plants are known as 25 plant growth-promoting rhizobacteria (PGPR). In this work, a multi-species of PGPR 26 bacteria inoculant was designed, which included nitrogen-fixing strains such as 27 Rhizobium phaseoli, Sinorhizobium americanum and Azospirillum brasilense, as well as 28 other plant growth promoting bacteria such as Bacillus subtillis and Methylobacterium 29 extorquens. The multi-species community exerted a beneficial effect on pl… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…The gene expression of Azospirillum lipoferum 4B during interaction with rice roots was assayed ( Drogue et al, 2014 ). A metatranscriptomic study was conducted to investigate the contributions of different nitrogen-fixing bacteria present in the maize inoculated liquid ( Gomez-Godinez et al, 2018 ). Metabolomics was applied to explore the exo-metabolome of three PGPB ( Pseudomonas putida IDE-01, Azospirillum brasilense IDE-06, and Bacilus megaterium IDE-14) in interaction with maize and rice ( Garcia et al, 2022 ).…”
Section: Omics Methods For Assaying Molecular Mechanisms Of Pgpbmentioning
confidence: 99%
“…The gene expression of Azospirillum lipoferum 4B during interaction with rice roots was assayed ( Drogue et al, 2014 ). A metatranscriptomic study was conducted to investigate the contributions of different nitrogen-fixing bacteria present in the maize inoculated liquid ( Gomez-Godinez et al, 2018 ). Metabolomics was applied to explore the exo-metabolome of three PGPB ( Pseudomonas putida IDE-01, Azospirillum brasilense IDE-06, and Bacilus megaterium IDE-14) in interaction with maize and rice ( Garcia et al, 2022 ).…”
Section: Omics Methods For Assaying Molecular Mechanisms Of Pgpbmentioning
confidence: 99%
“…Recently, using metatranscriptomic analysis, Gómez-Godínez et al (2019) revealed that Azospirillum nif genes were upregulated in the presence of other PGPR species, resulting in active nitrogen fixation by A. brasilense in maize roots [ 15 ]. Similarly, it was shown that the individual bacterial agents within PGPR communities differentially express their disease-suppressive traits [ 14 , 16 ], and accordingly induce the tuning of genes and metabolic pathways in host plants to achieve specific targets that benefit agriculture.…”
Section: Critical Approaches Towards Developing Successful Pgpr Mixturesmentioning
confidence: 99%
“…Multiple mechanisms of action have been postulated as to how this defense arises, including direct competition for nutrients and niches, antibiosis, enzyme lysis, signal interference and indirect induction of host resistance [ 7 , 8 , 10 , 11 , 12 ]. The accumulated evidence suggests PGPR taxa vary in the expression of traits [ 13 , 14 , 15 ] that correlate with one or more of the above mechanisms, thereby altering their capacities for protecting host plant from pathogens and thus promoting plant growth. Since PGPR live in communities on the root surface or sometimes inside the root (i.e., endophytes) and they are recruited by host plants, it has been deemed that each bacterial ‘component’ offers specific benefits for plants [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some of the PGPB act synergistically when applied together or coexist, such as B. subtilis with mycorrhizal fungi [ 9 , 19 ]. Gomez-Godinez et al revealed a stronger effect on maize when using multispecies inoculum of PGPB than single bacteria [ 131 ]. Inoculation with a single microbial culture may place the isolates in a worst position, because may suffer from competitive and deleterious effects of local soil microorganisms [ 108 , 132 ].…”
Section: Plant Growth Promoting Bacteria (Pgpb)mentioning
confidence: 99%